High‐precision 34S/32S measurements in vertebrate bioapatites using purge‐and‐trap elemental analyser/isotope ratio mass spectrometry technology. (14th August 2016) - Goedert, Jean; Fourel, François; Amiot, Romain; Simon, Laurent; Lécuyer, Christophe
Abstract : Rationale: In ecological studies, the sulfur isotope compositions (δ 34 S values) of soft tissues (e.g. hair, skin, nail, muscle, collagen) allow the determination of both past and present‐day living environments of organisms. However, technical limitations have so far prevented reliable sulfur isotope analyses of minerals having low sulfur content, such as bioapatite, which is the crystalline component of skeletal tissues. The development of 'purge‐and‐trap' technology in elemental analysers recently demonstrated new possibilities to solve some of those technical difficulties. Methods: We have used a VarioPYROcube elemental analyser (EA) equipped with 'purge‐and‐trap' technology, interfaced in continuous flow mode to an Isoprime 100 isotope ratio mass spectrometer, to measure the sulfur isotope compositions of bioapatite samples. We first characterised a working calibrated material of chemical composition close to those of our samples, the low‐S bearing phosphorite BCR32, against the two δ 34 SV‐CDT reference‐calibrated materials, NBS‐127 and IAEA‐SO‐5. We have confirmed a δ 34 SV‐CDT value of +18.4‰ (1 σ  = 0.5; n  = 18) in agreement with the previously published value. Using BCR32 as a compositional and isotopic reference material, we have then measured the δ 34 SV‐CDT values of various bioapatite tissues (bone, dentine and enamel) from both modern and fossil vertebrates living in different environments (marine, freshwater and terrestrial). Results: Our results demonstrate the capacity of this analytical setup to measure the δ 34 SV‐CDT values of low‐S bioapatite samples (0.14 to 1.19 wt%) with a good analytical precision (1 σ  = 0.5; n  = 14). Our results also show that the δ 34 SV‐CDT values of modern and fossil vertebrate bioapatites allow discrimination between marine environments and freshwater or terrestrial ones. Conclusions: Sulfur isotope analysis of bioapatite has great potential to track the living environment of extinct vertebrates for which only fossilised bones or teeth have been preserved. Copyright © 2016 John Wiley & Sons, Ltd.